A survey of paediatricians on the use of electrocardiogram for pre-participation sports screening. (10th October 2016) - Patel, Angira; Webster, Gregory; Ward, Kendra; Lantos, John
Abstract: Aim: The aim of the present study was to determine general paediatrician knowledge, practices, and attitudes towards electrocardiogram (ECG) screening in school athletes during pre-participation screening exam (PPSE). Methods: Paediatricians affiliated with a tertiary children's hospital completed a survey about ECGs for PPSE. Results: In total, 205/498 (41%) responded; 92% of the paediatricians did not include an ECG as part of PPSE; 56% were aware of a case in which a student athlete in their own community had died of sudden unexplained death; 4% had an athlete in their practice die. Only 16% of paediatricians perform all 12 American Heart Association recommended elements of the PPSE. If any of these screening elements are abnormal, 69% obtain an ECG, 36% an echocardiogram, and 30% restrict patients from sports activity; 73% of them refer the patient to a cardiologist. Conclusion: Most of the general paediatricians surveyed did not currently perform ECGs for PPSE. In addition, there was a low rate of adherence to performing the 12 screening elements recommended by the American Heart Association. They have trouble obtaining timely, accurate ECG interpretations, worry about potential unnecessary exercise restrictions, and cost-effectiveness. The practical hurdles to ECG implementation emphasise the need for a fresh look at PPSE, and not just ECG screening. Improvements in ECG performance/interpretation would be necessary for ECGs to be a useful part of PPSE.